2016
DOI: 10.1021/acs.langmuir.6b00675
|View full text |Cite
|
Sign up to set email alerts
|

Further Insight into the Definite Morphology and Formation Mechanism of Mesoporous Silica KCC-1

Abstract: The unique three-dimensional pore structure of KCC-1 has attracted significant attention and has proven to be different compared to other conventional mesoporous silica such as the MCM-41 family, SBA-15, or even MSN nanoparticles. In this research, we carefully examine the morphology of KCC-1 to define more appropriate nomenclature. We also propose a formation mechanism of KCC-1 based on our experimental evidence. Herein, the KCC-1 morphology was interpreted mainly on the basis of compiling all observation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 71 publications
2
58
0
Order By: Relevance
“…Recently, Febriyanti et al. also studied the mechanism of formation of DFNS by using gray value intensity patterns [generated from the transmission electron microscopy (TEM) images of DFNS], the critical micelle concentration (found by specific conductance measurements), and Raman spectroscopy. They observed different gray value patterns (U‐ and W‐shaped plots) for different silica morphologies.…”
Section: Synthesis and Mechanism Of Formation Of Dendritic Fibrous Namentioning
confidence: 60%
“…Recently, Febriyanti et al. also studied the mechanism of formation of DFNS by using gray value intensity patterns [generated from the transmission electron microscopy (TEM) images of DFNS], the critical micelle concentration (found by specific conductance measurements), and Raman spectroscopy. They observed different gray value patterns (U‐ and W‐shaped plots) for different silica morphologies.…”
Section: Synthesis and Mechanism Of Formation Of Dendritic Fibrous Namentioning
confidence: 60%
“…The TEOS introduced into the system as silica precursor in the organic phase hydrolyzes by interacting with the hydrophobic tail of the CTA + ions and water into polar products (silanol groups and ethanol) . Febriyanti et al reported a drop in pH from 8.14 to 6.89 indicated the hydrolysis occurred in basic medium.…”
Section: Resultsmentioning
confidence: 99%
“…KCC‐1 is usually synthesized via microemulsion involving an interaction between a surfactant, oil phase (such as toluene), and aqueous phase (usually water). The technique offers controlled tuning of morphology, surface area, and mesoporosity of variety of catalyst supports …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative mechanism was proposed by Febriyanti et al [40], considering the optimal conditions for the synthesis of KCC-1 [29]. They suggest the formation of reverse micelles in which the sol-gel reactions take place at higher rate in the center of the droplet.…”
Section: Synthesis Of the Hierarchical Meso/macroporous Sio 2 Spheresmentioning
confidence: 99%